Effects of healthy aging on internal brainstem structure. (31st December 2021) - Mueller, Susanne G
Abstract: Background: The brainstem is a complex structure and is often affected in the earliest stages of a neurodegenerative diseases. However, internal brainstem structures are not delineated on standard MR sequences complicating the differentiation between healthy aging and an incipient neurodegenerative process in‐vivo. The overall goal of this project was to characterize age‐related atrophy of different brainstem structures using a modification of a previously published multi‐contrast brainstem segmentation approach (1) using standard MR sequences. Method: The T1 and T2‐weighted images from 677 subjects (age range: 36‐100) of the Lifespan Human Connectome Project Aging were selected. Each subject's T1w and T2w were co‐registered, re‐scaled and a T1/T2ratio image calculated. After extracting the brainstem/thalamus, a k‐mean cluster analysis was used to identify 4 different brainstem tissue clusters based on the intensities from the 3 images. DARTEL was used to generate a population template from the brainstem tissue‐maps of 100 randomly selected subjects covering the whole age range. Each subjects tissue‐maps were warped onto this template and the Jacobian determinants calculated (Figure 1). The subjects were then divided into 6 groups (4th, 5th, 6th, 7th, 8th, 9th decade). SPM with threshold‐free cluster enhancement (p<0.005, FWE) was used for group comparisons. 58 gray and white matter brainstem regions‐of‐interest were used to extract voxels surpassing this statistical threshold to further characterize the age‐related volume loss. Result: See Figure 2 for abbreviations and detailed findings. Mesencephalic centers such as NR, CS, CI and PTPT showed age‐related volume loss starting at the age of 50. SN, VTA, and pontine centers such as NRPO, PB, NRPT, NRPC and medullary regions such as OI, NTS, VML, NRMOC and other major white matter tracts became atrophied starting at 60 and after 70 all 58 brainstem centers except for the DR and SC were atrophied. Conclusion: Age‐related brainstem atrophy starts in the mesencephalon and progresses to the pons and medulla and also affects white matter tracts. The pattern of age‐related atrophy reflects the timing of typical age‐related brainstem dysfunctions, e.g., age‐related hearing loss. This method might be useful for the early detection of neurodegenerative diseases starting in the brainstem. Reference: Hum Brain Mapp.2020;41:2173‐2186.